Spread of Knowledge on Olympism in School Applying the Integrated Programme of Olympic Education - Daiva Majauskienė; Saulius Šukys; Aušra Lisinskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. The present study deals with the Integrated Programme of Olympic Education in school. We hypothesized that pupils in schools where this program was executed would have more knowledge on Olympism. Research aim was to determine the possibilities of spreading the knowledge on Olympism in schools applying the programme of the Olympic education. Research methods. The sample consisted of the representative group of 2335 adolescents aged between 13 and 18 years. The study employed an Olympic Questionnaire (Olympic Questionnaire - Telama et al., 2002) in order to establish in what way the school provided Olympism-related information and what knowledge related to Olympism and Olympic Games the pupils possessed. Research results. It was established that the contents of the Olympic education was various: the pupils were acquainted with various historic facts about the Olympic Games, their participants, symbolism, traditions, Fair play; pupils performed practical tasks and various festivals were organized at schools. The survey showed that the knowledge of pupils from the schools executing the programme of the Olympic education about the ﬁ rst Modern and the last Olympic Games was better. More pupils from these schools knew the Paralympics Games. Discussion and conclusions. The survey showed that teachers from schools where the integrated programme of the Olympic education was executed integrated information about Olympism into their teaching subjects. Knowledge about the Olympic Games and their participants among pupils in these schools were much better as well. Keywords: Olympism, Integrated Olympic Education, Olympism-related knowledge.